Protein Conjugation via SpyStapler‐Mediated SpyTag/BDTag Coupling. Issue 4 (7th April 2021) - Da, Xiao‐Di; Wu, Xia‐Ling; Liu, Yajie; Zhang, Wen‐Bin
Abstract: Genetically encoded peptide‐protein coupling reactions, such as the SpyTag/SpyCatcher chemistry, are recent additions to the expanding toolbox of protein bioconjugation. The alternative three‐component ligation system, e.g., SpyStapler‐mediated SpyTag/BDTag coupling, retains most advantages of the Tag/Catcher chemistry, yet requires only two short peptide tags in the genetic fusion for side‐chain ligation. Not only does this facilitate the construction of large protein conjugates directly from as‐expressed protein components with minimal disruption to their function, but it also provides an entirely new mode of bioconjugation via mechanical bonding, which could impart additional functional benefits such as improved activity and enhanced stability to the conjugate. Such features are attractive for improving the pharmacokinetic performance of protein therapeutics. Herein we describe protocols for SpyStapler‐mediated SpyTag/BDTag coupling for protein bioconjugation. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Conjugation via isopeptide bond Support Protocol : Purification by size‐exclusion chromatography Basic Protocol 2 : Conjugation via mechanical bond